2021
DOI: 10.3390/coatings11020124
|View full text |Cite
|
Sign up to set email alerts
|

Laser Surface Texturing for Biomedical Applications: A Review

Abstract: For generating a texture or pattern on a work surface, one of the emerging processes is laser surface texturing (LST). It is an effective method for producing texture on a work surface. Literature shows that various lasers have been applied to generate textures on the surface of work materials. Recently, LST has shown tremendous potential in the field of biomedical applications. Applying the LST process, the efficacy of the biomaterial has been drastically improved. This paper presents an in-depth review of la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(38 citation statements)
references
References 92 publications
0
38
0
Order By: Relevance
“…One of the new processes of adding texture or picture onto the effective surface of polymer products is laser surface texturing (LST) [59]. A number of studies showed the high potential of LST for modifying and enhancing the effectiveness of biomedical materials.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the new processes of adding texture or picture onto the effective surface of polymer products is laser surface texturing (LST) [59]. A number of studies showed the high potential of LST for modifying and enhancing the effectiveness of biomedical materials.…”
Section: Introductionmentioning
confidence: 99%
“…Shivakoti et al [59] presented an in-depth review of laser surface texturing for biomedical applications. The researchers used various types of lasers, such as CO 2 laser, excimer laser, fiber laser, etc., to produce texture to explore the efficacy of the process and its impact on proliferation, osseointegration, cell adhesion, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The domain of these effects is important from diagnostic, clinical, and cosmetic aspects as the adaptation of color plays a key role [1][2][3]. Additionally, the effects of the laser light on mechanisms associated with cavity preparation and treating the surface of dentin [4,5] as well as the process of disinfection [6], and different dimensions of tissue regeneration are well evident [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…The domain of these effects is important from diagnostic, clinical, and cosmetic aspects as the adaptation of color plays a key role [1][2][3]. Additionally, the effects of the laser light on mechanisms associated with cavity preparation and treating the surface of dentin [4,5] as well as the process of disinfection [6], and different dimensions of tissue regeneration are well evident [7, 8].These effects are well used now and the applications of lasers and LEDs in various treatments of different areas of odontology have gained remarkable attention and proved highly e cient [9][10][11][12].…”
mentioning
confidence: 99%